Preparation process of chicken small peptide by enzymatic hydrolysis - YANG, XIUJUAN; ZHANG, XI; CAO, ZHIYONG; HUANG, WEI; TAO, LINLI; DENG, BIN; QI, MIN; CHEN, CHEN; SUN, ZHAOCHENG; ZHONG, XINGWEN (The Indian Journal of Animal Sciences, 2021)
The study optimized the enzymatic hydrolysis conditions for the production of small peptides composed of 2~3 amino acids from chicken. Experiment adapted 4 factors 3 levels orthogonal design, and result analysis showed that enzymatic hydrolysis condition has an effect on total nitrogen (T-N), total amino nitrogen (A-N), degree of hydrolysis (DH), nitrogen recovery (NR), average peptide chain length (APL) and average peptides molecular mass (APM). By main effect analysis, enzymolysis time was the main influencing factor of the DH, APL and APM. Solid-liquid ratio was the main influencing factor of NR, A-N and T-N. From quadratic curve between temperature and NR, optimal temperature can be obtained. The small peptides samples were analyzed using HPLC to find out the peptide content. These results indicated that method with simple equipment, mild reaction, and easy control, this provides a further theoretical basis for the production of meat peptides.